1991
DOI: 10.1038/354073a0
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spines as individual neuronal compartments for synaptic Ca2+ responses

Abstract: The possibility that postsynaptic spines on neuronal dendrites are discrete biochemical compartments for Ca(2+)-activated processes involved in synaptic plasticity is a widely proposed concept that has eluded experimental demonstration. Using microfluorometry on CA3 neurons in hippocampal slices, we show here that with weak presynaptic stimulation of associative/commissural fibres, Ca2+ accumulates in single postsynaptic spines but not in the parent dendrite. Stronger stimulation also promotes changes in dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
190
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(197 citation statements)
references
References 23 publications
5
190
2
Order By: Relevance
“…By virtue of the synaptic activation of NMDARs, Ca 2+ elevations within individual dendritic spines of hippocampal and neocortical pyramidal neurons during coincident EPSP-bAP trains have been shown to be larger than the predicted algebraic sum of Ca 2+ signals elicited by the subthreshold EPSP and bAP trains by themselves, i.e., they are supralinear (Yuste and Denk, 1995;Koester and Sakmann, 1998;Nevian and Sakmann, 2004). It is important to note that in the present manuscript we have not performed Ca 2+ measurements within spine heads, but rather in secondary apical dendrites, known to be studded with spines (Müller and Connor, 1991;Harris et al, 1992;Petrozzino et al, 1995;Pozzo-Miller et al, 1999). In addition, we have not addressed whether dendritic Ca 2+ signals evoked by different stimulation protocols have supra-or sublinear relationships, but rather calculated how much larger were the Ca 2+ signals evoked by coincident EPSP-bAPs compared to those evoked by bAPs alone.…”
Section: Discussionmentioning
confidence: 73%
“…By virtue of the synaptic activation of NMDARs, Ca 2+ elevations within individual dendritic spines of hippocampal and neocortical pyramidal neurons during coincident EPSP-bAP trains have been shown to be larger than the predicted algebraic sum of Ca 2+ signals elicited by the subthreshold EPSP and bAP trains by themselves, i.e., they are supralinear (Yuste and Denk, 1995;Koester and Sakmann, 1998;Nevian and Sakmann, 2004). It is important to note that in the present manuscript we have not performed Ca 2+ measurements within spine heads, but rather in secondary apical dendrites, known to be studded with spines (Müller and Connor, 1991;Harris et al, 1992;Petrozzino et al, 1995;Pozzo-Miller et al, 1999). In addition, we have not addressed whether dendritic Ca 2+ signals evoked by different stimulation protocols have supra-or sublinear relationships, but rather calculated how much larger were the Ca 2+ signals evoked by coincident EPSP-bAPs compared to those evoked by bAPs alone.…”
Section: Discussionmentioning
confidence: 73%
“…In neurons, action potential (AP) firing triggers large influxes of Ca 2+ through voltage-gated calcium channels located throughout the cell (Jaffe et al, 1992). Synaptic input causes local Ca 2+ influx through neurotransmitter receptors in dendritic spines and shaft (Muller and Connor, 1991). The spatiotemporal pattern of intracellular [Ca 2+ ] is tightly coupled to neural activity (Denk et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…There is now substantial evidence that changes in intracellular Ca 2ϩ occur during the induction of LTP and LTD (Regehr and Tank, 1990;Muller and Connor, 1991;Otani and Connor, 1998;Cormier et al, 2001) and are responsible for triggering the synaptic modifications. In particular, it has been shown that both these processes can be blocked by intracellular injection of Ca 2ϩ buffers (Lynch et al, 1983;Malenka et al, 1988;Mulkey and Malenka, 1992).…”
Section: Introductionmentioning
confidence: 99%